2014
DOI: 10.1002/app.40582
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mechanical properties of exfoliated graphite nanoplatelets reinforced polyethylene terephthalate/polypropylene composites

Abstract: Recently, graphene and its derivatives have been used to develop polymer composites with improved or multifunctional properties. Exfoliated graphite nanoplatelets (GNP) reinforced composite materials based on blend of polyethylene terephthalate (PET), and polypropylene (PP) compatibilized with styrene–ethylene–butylene–styrene‐g‐maleic anhydride is prepared by melt extrusion followed by injection molding. Characterization of the composites' microstructure and morphology was conducted using field emission scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 45 publications
6
29
0
Order By: Relevance
“…This result indicates that 15 phr is the optimum amount of SEBS ‐g‐ MA that can be added into the PET/PC/HNTs nanocomposites. In a related study, Inuwa et al . observed that 10 phr SEBS ‐g‐ MA is the optimum concentration for the effective compatibilization of PET/PP in PET/PP/GNP nanocomposites.…”
Section: Resultsmentioning
confidence: 96%
“…This result indicates that 15 phr is the optimum amount of SEBS ‐g‐ MA that can be added into the PET/PC/HNTs nanocomposites. In a related study, Inuwa et al . observed that 10 phr SEBS ‐g‐ MA is the optimum concentration for the effective compatibilization of PET/PP in PET/PP/GNP nanocomposites.…”
Section: Resultsmentioning
confidence: 96%
“…For PC/ABS blend, T 10 5 408, T 50 5 448, and T 80 5502 C, while for PC/ABS nanocomposite with 3 wt% GNPs content were increased to 424, 479, and 714 C, respectively. Even when the amount of GNPs was only 1 wt%, the T 10 temperature increased up to 20 C. The results are in agreement with previous work by Villar-Rodil et al [56] on poly (methyl methacrylate) (PMMA)/GNPs nanocomposites, which showed that the presence of the GNPs improved the thermal stability of the polymer, as the degradation process is shifted to higher temperatures by around 10 C with 1 wt% GNPs loading and the degradation rate became slower. The data analysis clearly shows two decomposition temperatures (DTG) for nanocomposites.…”
Section: Thermogravimetric Analysismentioning
confidence: 97%
“…Graphene have begun to be explored to improve the flammability properties of various polymer systems. For example, GNP has been used as intumescent flame retardant in Polycarbonate nanocomposite [27], polyethylene terephthalate (PET)polypr/opylene (PP) blend [28], polyisocyanurate (PIR)/polyurethane (PU) [29] and high-density rigid polyurethane (RPU) [30] with an overall improvement of the fire behavior and no worsening of the mechanical properties. The addition of GNP, even at low concentration level (usually less than 5%), into a polymeric matrix can significantly improve polymer properties such as flammability, thermal behavior, mechanical properties, electrical conductivity and gas barrier properties [31][32][33][34][35].…”
Section: A N U S C R I P Tmentioning
confidence: 99%